Deteksi Kerusakan Motor Induksi Dengan Menggunakan Sinyal Suara - Akbar Anggriawan; Feblil Huda (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Induction motor plays an important role in the industrial realm that serves as a driving parts such as the conveyor, lathes and others. Regarding to this important role, the early detection of induction motor damage becomes important for system operation, so that it could not stopped without scheduled. The types of damage that often occur in induction motor are mechanical unbalance, rotor damage and bearing damage. The usual detection method which uses vibration measurments has some disadvanteages such as it is very expensive, physical contact with the induction motor that occurs and the sensors are less heat resistant on induction motor. The author uses sound signal detection method that is cheaper regarding to the cost, it has no physiscal contact with the induction motor and heat resistant. The sound signal is generated by the exicitation of the artificial damage which is provided to the induction motor. Artificial damage is given by damaging the bearing, rotor and mass unbalance. Sound signal data from artificial damage test result on induction motor is processed by using fast fourier transform method. The result of the research obtains the amplitude increased number for one time motor rotation 2970 rpm (1xrpm) is 49.5 Hz, 144.5 Hz for bearing damage frequency and 78.5 Hz for the rotor damage frequency.Keywords : Induction motor, mechanical unbalance, bearing, rotor, signal sound, fast fourier transform